Influence of social networks on young adults from the first level at Administration and Marketing careers at Universidad de las Fuerzas Armadas-ESPE - Salguero Recalde, Delanie (2022)
This research took place at Universidad de las Fuerzas Armadas espe, and it was applied to first semester students from school of Administration and Marketing; the main goal is focused on the study of this students’ behaviour during the covid-19 pandemic based in four perspectives: interpersonal, familiar, emotional, and academic. It was designed a questionnaire for the students of methodology course for both women and men; previous investigations on this field were analyzed too. After reviewing the literature related to social networks and the factors previously mentioned, it was made a survey to know the direct influence on students. Once the data was collected and observed, the results determined some important facts related to social networks and their effects on students art of human dignity.